PELATIHAN PEMBUATAN MEDIA FOTONOVELA MENGGUNAKAN CANVA UNTUK GURU DI KECAMATAN LIMBANGAN GARUT - Hardiani, Santi (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2025)
Teacher competency development needs to be continuously trained and improved. The results of observations and findings show that there are still many teachers who have difficulties in creating effective learning media, especially in adapting technology to increase the attractiveness and understanding of students. Therefore, systematic training is needed to improve teachers' competence in creating innovative learning media. One of the solutions offered is the use of photonovela, an image and text-based learning media that resembles comics, which can help present teaching materials in a more interesting and easy-to-understand manner. This training program is designed to provide teachers with conceptual understanding and practical skills in creating photonovela media using Canva. This training is carried out through three main stages, namely planning, implementation, and evaluation of training results. The methods used include material presentations, discussions and questions and answers, as well as direct practice by participants. The results obtained show that this training has succeeded in improving teachers' competence in using Canva to create photonovelas as a learning medium. Teachers who take part in the training are able to create learning media that are more creative, interesting, and in accordance with the needs of students. Thus, this program is expected to have a positive impact on improving the quality of learning in Limbangan District, Garut.